Rainwater management in the Nile Basin—Reflections on a stakeholder workshop in Bahir Dar - Mengistu, F. (International Livestock Research Institute, 2012)
In October 2011, project partners and team members in the Nile Basin Development Challenge (http://www.nilebdc.org) met in Bahir Dar, Ethiopia to reflect on project progress and directions. Here, Fantahun Mengistu, Director of the Amhara Regional Agricultural Research Institute (ARARI), shares some lessons and take home messages from the meeting. He noted that, although a good national policy framework is in place, there are some gaps in implementation at grassroots level: including proper integration between water and agriculture, more emphasis given to blue than to green water, and fully understanding the farmers and the farmer circumstances – “we need to know very well the farmer.” Sustainability is a key issue, it needs increased participation of communities, more emphasis on showing short term benefits to farmers, increased attention to integrated hydrological planning at basin and landscape level – we need to ensure that people getting upstream benefits does not mean that people downstream will suffer.